FALL INTO THE (INTERTEXTUAL) GAP: PROVERBS, ADVERTISEMENTS AND INTERTEXTUAL STRATEGIES - Winick, Stephen D. (Proverbium - Yearbook, 2018)
This paper is an analysis of the specific ways in which American advertisements use proverbs and proverbial phrases to persuade. It proceeds from an understanding of the proverb as an essentially intertextual phenomenon: an entextualized utterance, based on previous similar utterances, which can in turn be quoted, imitated, or manipulated to produce specific instances of proverbial communication. It employs the idea of the “intertextual gap,” theorized by Charles Briggs and Richard Bauman, and postulates that proverbial advertisements create and manipulate intertextual gaps to make meaning. It demonstrates that, through the use of the intertextual gap, proverbial ads can use the authority inherent in the proverb, they can challenge the authority of particular proverbs, or they can challenge the authority of the whole proverb tradition. In all of these cases, the ad claims as its own either the wisdom of the proverb, or a wisdom greater than that of the proverb, in the hopes of persuading audiences. It shows that some ads create fictive worlds, and inside those fictive worlds, coin proverbs, which then have a chance to emerge into everyday speech. It further shows that the language play demonstrated by clever proverb ads gives audiences pleasure, fulfilling a societal need for public poetry, and that this enhances the ad’s selling power.